Peculiarities of the interblock boundary constitution in a layered structure of compounds of the AnBn−1O3n-type - Titov, Yu.A.; Belyavina, N.M.; Slobodyanik, M.S.; Chumak, V.V. (Reports of the National Academy of Sciences of Ukraine, 2017)
Peculiarities of the interblock boundary constitution in a layered perovskite-like structure (LPS) of compounds of the AnBn−1O3n-type have been analyzed. A number of interrelations between the composition of AnBn−1O3n-type compounds, the thickness of their perovskite-like blocks, and the constitution of their interblock boundaries in LPS have been revealed. It has been established that the values of degree of a deformation of external block polyhedra AO12 and the lengths of the interblock A—O bond are ones of the main factors, which determine the stability of LPS of compounds of the AnBn−1O3n-type.